Preventive effects of yogurt fortified with purple roselle extract against cardiotoxicity in rats exposed with 2,3,7,8-tetrachlorodibenzo-p-dioxin - Setianingrum, Ani; Fanadila, Iffa; Pratiwi, Herlina; Haskito, Ajeng Erika Prihastuti (The Journal of Experimental Life Science, 2021)
Dioxin is one of the environmental persistent organic pollutants that harm animal and human health. Prolonged exposure to 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) can disrupt normal organ function including heart. Yogurt is known to have antioxidant properties, and fortification natural plant-based antioxidant purple roselle (Hibiscus sabdariffa L) extract into yogurt can improve the antioxidant potential. The purpose of this study was to determine the preventive effect of yogurt fortified with purple roselle on dioxin exposure rats (Rattus norvegicus) based on the levels of Malondialdehyde (MDA) and histopathological of the heart. This experimental study using a completely randomized design (CRD). A total of 30 male Wistar rats were divided into 5 groups (NC, PC, T1, T2, T3), a dose of 200 ng/kg BW TCDD and 1 mL of roselle yogurt 0.5%, 1.0%, and 1.5% were given orally for 12 days. MDA levels were analyzed using the Thiobarbituric Acid (TBA) assay and histopathology of the heart using the Haematoxylin Eosin (HE) staining method. Statistical analysis using one-way Analysis of Variance (ANOVA). Histopathology changes were analyzed descriptively. The results showed that TCDD exposure induced oxidative stress in heart tissue and yogurt roselle has the potential to prevent an increase of MDA levels significantly (p<0.05). Furthermore, TCDD can cause histopathological alterations such as necrosis and hemorrhage, and yogurt roselle was proven to prevent cardiotoxicity due to TCDD exposure.